Landscape of pathogenic variations in a panel of 34 genes and cancer risk estimation from 5131 HBOC families. (December 2018) - Castéra, Laurent; Harter, Valentin; Muller, Etienne; Krieger, Sophie; Goardon, Nicolas; Ricou, Agathe; Rousselin, Antoine; Paimparay, Germain; Legros, Angelina; Bruet, Olivia; Quesnelle, Céline; Domin, Florian; et al.
Abstract Purpose Integration of gene panels in the diagnosis of hereditary breast and ovarian cancer (HBOC) requires a careful evaluation of the risk associated with pathogenic or likely pathogenic variants (PVs) detected in each gene. Here we analyzed 34 genes in 5131 suspected HBOC index cases by next-generation sequencing. Methods Using the Exome Aggregation Consortium data sets plus 571 individuals from the French Exome Project, we simulated the probability that an individual from the Exome Aggregation Consortium carries a PV and compared it to the estimated frequency within the HBOC population. Results Odds ratio conferred by PVs withinBRCA1, BRCA2, PALB2, RAD51C, RAD51D, ATM, BRIP1, CHEK2, andMSH6 were estimated at 13.22 [10.01– 17.22], 8.61 [6.78– 10.82], 8.22 [4.91– 13.05], 4.54 [2.55– 7.48], 5.23 [1.46– 13.17], 3.20 [2.14– 4.53], 2.49 [1.42– 3.97], 1.67 [1.18– 2.27], and 2.50 [1.12– 4.67], respectively. PVs withinRAD51C, RAD51D, andBRIP1 were associated with ovarian cancer family history (OR = 11.36 [5.78– 19.59], 12.44 [2.94– 33.30] and 3.82 [1.66– 7.11]).PALB2 PVs were associated with bilateral breast cancer (OR = 16.17 [5.48– 34.10]) andBARD1 PVs with triple-negative breast cancer (OR = 11.27 [3.37– 25.01]). Burden tests performed in both patients and the French Exome Project population confirmed the association of PVs ofBRCA1, BRCA2, PALB2, andRAD51C with HBOC. Conclusion Our results validate the integration ofPALB2, RAD51C, andRAD51D in the diagnosis of HBOC and suggest that the other genes are involved in an oligogenic determinism.